Work, your way : reinvent yourself, create the life you want and thrive as a consultant - Hufford, Lisa (HarperCollins Leadership, 2021)
"Build your successful consultant life doing the work you love, on your terms utilizing the practical tips, inspiration, and straightforward advice from recognized new world of work visionary and thought leader, Lisa Hufford." -- Amazon.com.